2018
DOI: 10.1016/j.bjan.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre síndrome da apneia obstrutiva e via aérea difícil na cirurgia otorrinolaringológica

Abstract: The STOP Bang questionnaire was not able to predict difficult airway and mild obstructive sleep apnea syndrome, but it identified marked obstructive sleep apnea syndrome. All patients with difficult airway had moderate and marked obstructive sleep apnea syndrome, although this syndrome did not involve difficult airway. The variables Cormack III/IV and BMI greater than 35 Kg.m were able to predict difficult airway and obstructive sleep apnea syndrome, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study utilizing a questionnaire to predict difficult airway among patients diagnosed with OSA undergoing ENT surgery reported that 18.7% of patients with OSA syndrome have difficult airways of Cormack III/IV. [ 12 ] Measures such as “proper body and head position, sufficient preoxygenation, effective airway maneuvers, and continuous assessment of ventilation may help to reduce respiratory complications during anesthesia induction”. [ 13 ] In our case, monitoring was performed with plethysmograph, capnograph, and electrocardiogram.…”
Section: Discussionmentioning
confidence: 99%
“…A study utilizing a questionnaire to predict difficult airway among patients diagnosed with OSA undergoing ENT surgery reported that 18.7% of patients with OSA syndrome have difficult airways of Cormack III/IV. [ 12 ] Measures such as “proper body and head position, sufficient preoxygenation, effective airway maneuvers, and continuous assessment of ventilation may help to reduce respiratory complications during anesthesia induction”. [ 13 ] In our case, monitoring was performed with plethysmograph, capnograph, and electrocardiogram.…”
Section: Discussionmentioning
confidence: 99%